Zwitterionic Molecularly Imprinted Hairy Cellulose Nanocrystals Enable Selective Vancomycin Removal - Koshani, Roya (Langmuir : the ACS journal of surfaces and colloids, 2025)
Access to free, off-target, and nontherapeutic doses of antibiotics is a key driving factor in the emergence of antimicrobial resistance (AMR). Intravenously (IV) administered vancomycin (VAN) is among the last-line antibiotics for treating infections caused by multidrug-resistant Gram-positive bacteria. A fraction of the total IV dose unwantedly reaches the gastrointestinal tract, driving AMR. Selective VAN removal from the complex intestinal fluid may reduce the probability of AMR emergence; however, it remains a significant challenge due to the competitive adsorption of other species. Here, we engineer novel VAN-imprinted polymerized zwitterionic hairy cellulose nanocrystals (ViPZ-HCNC) that selectively capture VAN with a removal capacity of ∼ 235 mg g-1 at an imprinting factor of ∼ 7.5. ViPZ-HCNC provide the first nanocellulose-based material with an excellent selectivity for VAN against lysine, lysozyme, and bovine serum albumin, which efficiently remove VAN from calcium ion-containing solutions and simulated intestinal fluids. Additionally, ViPZ-HCNC are not toxic against NIH/3T3 murine fibroblast cells. We envision that ViPZ-HCNC may pave the way for developing soft materials that selectively remove off-target VAN from a broad range of media, preventing VAN resistance evolution. This research is a step forward in addressing the long-lasting AMR challenge using a biobased platform